Isu-isu dan Alternatif dalam Filosofi Pendidikan - Sigiro, Adi Suhenra (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Through reading this book, both churches and schools are taught to reconstruct or reorganize what is the basis or philosophy of the church or school being established. Because the right foundation will determine how the church carries out its duties and achieves what goals it wants to achieve. Likewise with schools, the right philosophy will influence the sustainability of its implementation. The philosophy or motto of the church and school in carrying out its duties should be based on the Bible, so that in carrying out its duties there are no deviations. For churches and schools, philosophy is important because it will help to formulate church and school teachings systematically, coherently and comprehensively. Philosophy should be a tool in developing the ministry of the church and school. Through reading the book, various general theories about education can be seen. Various understandings create various theories and practices of education. Therefore, the ideas built in these understandings can be applied to build education or fostering congregation members. However, the church needs to be critical when the various theories offered are not in accordance with the values of the truth of God's word. The church must remember that both the congregation and the teachers and the goals of education must be constructed based on biblical values.